Survival Rate of Patients with Acute Leukemia in Iran: A Systematic Review and Meta-analysis - Roohollah Askari; Mohammad Ranjbar; Mehran Nakhaeizadeh; Shiva Sheikholeslami; Sara Sepehrifar; Morteza Adhami; Zeinab Shabooni (Shahid Sadoughi University of Medical Sciences, 2018)
Background: Leukemia is the fifth most common cancer among both genders. The prevalence of this type of cancer has been increasing in Iran. According to the Iranian Cancer Registry System, leukemia is among the first four cancer cases in terms of causing mortality. Considering the importance of survival rate of patients with acute cancers in Iran, this study aimed to study survival of patients with acute adult leukemia in Iran systematically. Methods: In this study, all articles on the survival rate of patients with acute leukemia were searched throughout the Google scholar,web of science, PubMed, Scopus, Cochrane of science, Cochrane, Magiran, Irandoc, IranMedex and SID websites. Our search included the articles published up toJune 2017. Using the keywords of Iran, ، Leukemia, ، Survival rate, blood cancer, life expectancy and their compositions. The search process was completed by two researchers independently. Then, all the reviewed articles and theses that met our inclusion criteria were examined. The data were analyzed using a comprehensive meta-analysis software and by running the Cochran test. Results: We investigated eight studies with a sample of 1219 people in our meta-analysis. The findings showed that the 1-year survival rate for adults with acute leukemia was 61 % and the 5-year survival rate was 48 %. Conclusion: According to the research findings, the survival rate of patients with acute leukemia in Iran is the same as other countries.